2013
DOI: 10.3390/nano3010070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Sonication Temperature on the Debundling Kinetics of Carbon Nanotubes in Propan-2-ol

Abstract: The effect of sonication temperature on the debundling of carbon nanotube (CNT) macro-bundles is reported and demonstrated by analysis with different particle sizing methods. The change of bundle size over time and after several comparatively gentle sonication cycles of suspensions at various temperatures is reported. A novel technique is presented that produces a more homogeneous nanotube dispersion by lowering the temperature during sonication. We produce evidence that temperature influences the suspension s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 66 publications
(79 reference statements)
0
23
0
Order By: Relevance
“…GO thin films were processed by first sonicating a 50 mL volume of the processed GO suspension in the same conditions previously described in order to de-stack potentially agglomerated GO sheets in a fashion similar to that previously reported [39]. The GO films were formed by vacuum filtration with a houseline vacuum on alumina membranes prior to vacuum drying at room temperature for at least 6 h. The GO films were then gently peeled from their filter membranes to form free-standing GO films made of tightly stacked GO sheets [9].…”
Section: Fabrication Of Freestanding Go Films and Gamma Ray Irradiationmentioning
confidence: 99%
“…GO thin films were processed by first sonicating a 50 mL volume of the processed GO suspension in the same conditions previously described in order to de-stack potentially agglomerated GO sheets in a fashion similar to that previously reported [39]. The GO films were formed by vacuum filtration with a houseline vacuum on alumina membranes prior to vacuum drying at room temperature for at least 6 h. The GO films were then gently peeled from their filter membranes to form free-standing GO films made of tightly stacked GO sheets [9].…”
Section: Fabrication Of Freestanding Go Films and Gamma Ray Irradiationmentioning
confidence: 99%
“…The water permeation rate of this new type of nano-filtration membrane is achieved by controlled corrugation of the graphene sheets through hydrothermal treatment of the chemically converted graphene suspension prior to vacuum filtration [14]. The chemical interactions between graphene nano-materials, primarily relying on van der Walls interactions render GO and pure graphene based assemblies relatively fragile and sensitive to swelling by hydration [24,25]. These disadvantages may be overcome by intercalating well-dispersed graphene nanosheets across a polymeric matrix to promote water transport and improve membrane performance [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the temperature flow during PCR could also accelerate the traffic of MWCNTs in suspension, hence the bundle formation due to the increased contact of the molecules. For example, Dumèe et al clearly observed larger CNT bundles in the suspensions sonicated at 60°C and above (Dumée et al 2013), which advocates the Einstein's theory of Brownian motion.…”
Section: Resultsmentioning
confidence: 87%
“…DLS technique provides a hydrodynamic size distribution calculated via the Stokes-Einstein equation from the dynamic fluctuations of light scattering intensity which is generated from Brownian motion of the spherical particles. Although DLS technique assumes particles as perfect spheres, it still could provide valuable information for CNT's hydrodynamic size distribution as previously reported (Isobe et al 2006;Moon et al 2009;Pease et al 2009;Krause et al 2010;Dumée et al 2013), based on CNT length and diameter by using the following equations:…”
Section: Dls Measurementsmentioning
confidence: 98%